Aggressive Local Treatment Improves Survival in Stage IV Breast Cancer With Synchronous Metastasis - Lian, Chen-Lu; Guo, Li-Yi; Zhang, Lei; Wang, Jun; Lei, Jian; Hua, Li; He, Zhen-Yu; Wu, San-Gang (Frontiers in Oncology, 2020)
Introduction To investigate the effect of local treatment strategy on survival outcome in de novo stage IV breast cancer patients who received chemotherapy. Methods We identified stage IV breast cancers that presented with synchronous metastasis from the Surveillance, Epidemiology, and End Results database. Binomial logistic regression, Kaplan–Meier survival curves, propensity score matching (PSM), and multivariate Cox regression model were used for statistical analyses. Results We identified 5,374 patients in total, including 2,319 (43.2%), 2,137 (39.8%), and 918 (17.1%) patients who received surgery alone, surgery+radiotherapy, and radiotherapy alone, respectively. The probability of patients receiving surgery alone decreased over time, and the probability of patients receiving radiotherapy alone increased over time. However, no significant difference was observed in the probability of patients receiving postoperative radiotherapy (P = 0.291). The 3-year breast cancer-specific survival (BCSS) in patients treated with surgery alone, radiotherapy alone, and surgery+radiotherapy was 57.1, 35.9, and 63.9%, respectively (P < 0.001). The local treatment strategy was the independent prognostic factor related to BCSS. Using surgery alone as the reference, radiotherapy alone was related to lower BCSS (P < 0.001), while additional radiotherapy after surgery improved BCSS (P < 0.001). Similar results were observed using PSM. Conclusions Compared to radiotherapy alone, surgery to the primary site may confer a survival benefit in stage IV breast cancer with synchronous metastasis, and additional postoperative radiotherapy further improves outcome after primary tumor removal. Local treatment can only be an option in highly selected patients with de novo stage IV disease in the treatment guidelines. More prospective studies are needed to investigate the role of local management for this patient subset.